Increasing the Effectiveness of Caregiver Education Through Program Evaluation Using the CIPP Method - Rahmat Darsono; Soewarto Hardhienata; Eka Suhardi (UJoST- Universal Journal of Science and Technology, 2023)
This study focuses on evaluating caregiver education in Indonesia using CIPP analysis, namely, Context, Input, Process and Product. In the following discussion, the language is translated into context, input, process and product or CIPP. So that later it is expected to be able to identify several aspects that can be used as input for stakeholders for the development of caregiver education. This evaluation research uses the CIPP approach to determine the effectiveness of the implementation of caregiver programs in Indonesia.The type of research used is descriptive evaluative, in which this research seeks to obtain various information on the implementation of caregiver education programs at SMK Darmawan and SMKN 8 Semarang. In this study the method of collecting data was through 3 ways, namely: 1) interviews, 2) documentation studies, 3) observation. In this research. Researchers use three ways; interviews with informants or resource persons who are considered competent in their field, Observation, in this study on site observation or observation at school by looking directly at all activities that are related to the process of caregiver education in educational units, next is documentation study, namely making validation of what the informants have explained about the program being implemented. In this research interviews were conducted with 5 informants according to their respective capacities according to Context, Input, Process and Product in CIPP sequentially. The need to open family caregivers does not refer to clear documents issued by the Ministry of Education and Culture. There were no definite documents regarding the need for caregivers quantitatively. In general, the vision of education can be properly reviewed. However, if we narrow it down to the opening of family caregivers, it is not specifically clear. It's just that the values of being knowledgeable, capable, creative, and independent are the basic things that must be the goals of family caregiver education, because they have to help the elderly properly. As already stated that the mission is a process that must be carried out to achieve the vision, the mission in opening the Carriver Family Card, although not implicitly mentioned in the educational mission, is to provide knowledge, skills and attitudes that are of global standard because there is indeed a need for caregiver workers. abroad quite a lot.